How Managers Find Out About Common Mental Disorders Among Their Employees. Issue 11 (4th November 2021) - Bertilsson, Monica; Klinkhammer, Stephanie; Staland-Nyman, Carin; de Rijk, Angelique
Abstract : Objective: To explore how managers find out about common mental disorders (CMDs) among employees and associations with managers' work- and knowledge-related characteristics and attitude to CMDs. Methods: Data from an online survey in 2017 with Swedish managers ( n  = 1810) were used. Different ways managers find out about CMDs were measured, and multivariate logistic regression analysis was conducted for associations with manager characteristics. Results: Few managers found out about CMDs themselves; another source was more common, for example, employees' self-disclosure. Managers' overseeing fewer subordinates and those with a negative attitude to depression were more likely to find out about CMDs themselves. The significance of mental health training and education could not be established. Conclusion: Managers' awareness about employees' CMDs mainly came about through employees' self-disclosure. Managers' attitudes and work conditions were related to the way of finding out.